Understanding Subterranean Hydrology in the Delineation of Wetlands : an Ephemeral Hillslope Wetland on Basement Granite in South Africa - Dippenaar, Matthys Alois (University of Pretoria, 2015)
Dissertation (MSc)--University of Pretoria, 2015.